Parameters, practices, and preferences for regulatory review of emerging biotechnology products in food and agriculture - Kuzma, Jennifer; Grieger, Khara; Cimadori, Ilaria; Cummings, Christopher L.; Loschin, Nick; Wei, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
This paper evaluates the U.S. regulatory review of three emerging biotechnology products according to parameters, practices, and endpoints of assessments that are important to stakeholders and publics.First, we present a summary of the literature on variables that are important to non-expert publics in governing biotech products, including ethical, social, policy process, and risk and benefit parameters.Second, we draw from our USDA-funded project results that surveyed stakeholders with subject matter expertise about their attitudes towards important risk, benefit, sustainability, and societal impact parameters for assessing novel agrifood technologies, including biotech. Third, we evaluate the regulatory assessments of three food and agricultural biotechnology case studies that have been reviewed under U.S. regulatory agencies and laws of the Coordinated Framework for the Regulation of Biotechnology, including gene-edited soybeans, beef cattle, and mustard greens. Evaluation of the regulatory review process was based on parameters identified in steps 1 and 2 which were deemed important to both publics and stakeholders. Based on this review, we then propose several policy options for U.S. federal agencies to strengthen their oversight processes to better align with a broader range of parameters to support sustainable agrifood products that rely on novel technologies. These policy options include 1) those that would not require new institutions or legal foundations (such as conducting Environmental Impact Statements and/or requiring a minimal level of safety data), 2) those that would require a novel institutional or cross-institutional framework (such as developing a publiclyavailable website and/or performing holistic sustainability assessments), and 3) those that would require the agencies to have additional legal authorities (such as requiring agencies to review biotech products according to a minimal set of health, environmental, and socio-economic parameters).Overall, the results of this analysis will be important for guiding policy practice and formulation in the regulatory assessment of emerging biotechnology products that challenge existing legal and institutional frameworks.